2013
DOI: 10.1111/jgh.12069
|View full text |Cite
|
Sign up to set email alerts
|

Sex, ethnicity, and slow acetylator profile are the major causes of hepatotoxicity induced by antituberculosis drugs

Abstract: This study showed that a patient's NAT-2 acetylator status, gender, and ethnic origin may be regarded as important risk factors for developing hepatotoxicity. Contrary to expectations, the CYP2E1 c1/c2 polymorphism did not show a significant association with hepatotoxicity in this study. Given the increases in TB cases and ATDH incidence levels, as well as the associated hospitalization costs, it may also be helpful to know patients' acetylator status prior to or at the beginning of the TB treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 28 publications
7
46
0
Order By: Relevance
“…NAT2 is one of the factors responsible for genetic predisposition to INH-induced hepatitis and NAT2 acetylating status is related to the patient's condition, sex and ethnic origin, so it may be regarded as important risk factor for the development of hepatotoxicity (Mahmoud et al 2012, Chamorro et al 2013.…”
Section: Association Among Clinical Factors Genotypes and Atd-inducementioning
confidence: 99%
See 1 more Smart Citation
“…NAT2 is one of the factors responsible for genetic predisposition to INH-induced hepatitis and NAT2 acetylating status is related to the patient's condition, sex and ethnic origin, so it may be regarded as important risk factor for the development of hepatotoxicity (Mahmoud et al 2012, Chamorro et al 2013.…”
Section: Association Among Clinical Factors Genotypes and Atd-inducementioning
confidence: 99%
“…The frontline drug, INH, has been extensively studied (Cheng et al 2013). In the human liver, INH is first acetylated by N-acetyltransferase 2 (NAT2) into acetylhydrazine, then oxidized into toxic intermediaries by cytochrome P450 2E1 (CYP2E1) (Huang et al 2003, Chamorro et al 2013). The toxic compounds produced are detoxified by further acetylation by NAT2 and by conjugation reactions catalyzed by glutathione S-transferase enzymes (GST).…”
Section: Introductionmentioning
confidence: 99%
“…TB is a re-emerging infectious disease with a high level of hepatotoxicity (25.6%) in hospitalized TB patients in Argentina [19]. Therefore, the present survey investigated the environmental factors and pharmacogenetic variation involved in INH metabolism and evaluated their association with ATDH independently and/or through complex interactions between them in a sample of hospitalized TB patients in Buenos Aires.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of the pharmacogenetics of TB found an association between genetic variations in these enzymes and ATDH development [10,[19][20][21]. The NAT2 gene was studied widely, and several surveys found an association between the slow acetylator phenotype and ATDH development [10,19,20,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation